Wykorzystanie zrównoważonej karty wyników w zarządzaniu ryzykiem przedsiębiorstwa - Szydełko, Łukasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Balanced Scorecard consists of four perspectives such as finance, client, internal processes and innovation and growth. This instrument enables to translate the strategy into action. The strategic goals which are in the strategy should be cascaded at lower levels in a company. We should choose internal parts (segments) in enterprises in which we provide the scorecard. In the internal parts we have risky situation. It determines that Balanced Scorecard should be connected with Enterprise Risk Management System. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 434-439